Gene therapy targets in heart failure: the path to translation - Raake, Philip; Tscheschner, Henrike; Reinkober, J.; Ritterhoff, Julia; Katus, Hugo; Koch, W. J.; Most, Patrick (Clinical pharmacology & therapeutics, 2011)
Heart failure (HF) is the common end point of cardiac diseases. Despite the optimization of therapeutic strategies and the consequent overall reduction in HF-related mortality, the key underlying intracellular signal transduction abnormalities have not been addressed directly. In this regard, the gaps in modern HF therapy include derangement of β-adrenergic receptor (β-AR) signaling, Ca2+ disbalances, cardiac myocyte death, diastolic dysfunction, and monogenetic cardiomyopathies. In this review we discuss the potential of gene therapy to fill these gaps and rectify abnormalities in intracellular signaling. We also examine current vector technology and currently available vector-delivery strategies, and we delineate promising gene therapy structures. Finally, we analyze potential limitations related to the transfer of successful preclinical gene therapy approaches to HF treatment in the clinic, as well as impending strategies aimed at overcoming these limitations. Clinical Pharmacology & Therapeutics (2011) 90 4, 542-553. doi:10.1038/clpt.2011.148